Characterizations of a Class of Dirichlet-Type Spaces and Related Operators - Xiaosong Liu; Songxiao Li (Journal of Mathematics)
In this paper, some characterizations are given in terms of the boundary value and Poisson extension for the Dirichlet-type space Dμ. The multipliers of Dμ and Hankel-type operators from Dμ to L2PμdA are also investigated.